Direct impact of COVID-19 vaccination in Chile: averted cases, hospitalizations, ICU admissions, and deaths - Antoine Brault; Andrew Hart; Paula Uribe; Jorge Prado; Jaime San Martín; Alejandro Maass; Mauricio Canals (BMC Infectious Diseases, 2024)
Abstract Background Chile rapidly implemented an extensive COVID-19 vaccination campaign, deploying a diversity of vaccines with a strategy that prioritized the elderly and individuals with comorbidities. This study aims to assess the direct impact of vaccination on the number of COVID-19 related cases, hospital admissions, ICU admissions and deaths averted during the first year and a half of the campaign. Methods Via Chile’s transparency law, we obtained access to weekly event counts categorized by vaccination status and age. Integrating this data with publicly available census and vaccination coverage information, we conducted a comparative analysis of weekly incidence rates between vaccinated and unvaccinated groups from December 20, 2020 to July 2, 2022 to estimate the direct impact of vaccination in terms of the number of cases, hospitalizations, ICU admissions and deaths averted, using an approach that avoids the need to explicitly specify the effectiveness of each vaccine deployed. Results We estimated that, from December 20, 2020 to July 2, 2022 the vaccination campaign directly prevented 1,030,648 (95% Confidence Interval: 1,016,975-1,044,321) cases, 268,784 (95% CI: 264,524-273,045) hospitalizations, 85,830 (95% CI: 83,466-88,194) ICU admissions and 75,968 (95% CI: 73,909-78,028) deaths related to COVID-19 among individuals aged 16 years and older. This corresponds to a reduction of 26% of cases, 66% of hospital admissions, 70% of ICU admissions and 67% of deaths compared to a scenario without vaccination. Individuals 55 years old or older represented 67% of hospitalizations, 73% of ICU admissions and 89% of deaths related to COVID-19 prevented. Conclusions This study highlights the role of Chile's vaccination campaign in reducing COVID-19 disease burden, with the most substantial reductions observed in severe outcomes.